2006
DOI: 10.1093/nar/gkl357
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylation of ribosomal RNA in human cells

Abstract: The addition of poly(A)-tails to RNA is a process common to almost all organisms. In eukaryotes, stable poly(A)-tails, important for mRNA stability and translation initiation, are added to the 3′ ends of most nuclear-encoded mRNAs, but not to rRNAs. Contrarily, in prokaryotes and organelles, polyadenylation stimulates RNA degradation. Recently, polyadenylation of nuclear-encoded transcripts in yeast was reported to promote RNA degradation, demonstrating that polyadenylation can play a double-edged role for RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 48 publications
5
91
1
1
Order By: Relevance
“…A nuclear RNA surveillance mechanism involving polyadenylation and rapid degradation of nonfunctional, antisense, and noncoding RNAs has been described in yeast and human cells (4,9,(33)(34)(35)(36). We initially assumed that the truncated, polyadenylated rRNA molecules that we had previously detected in human cells (18) are solely related to this process, but in this study we found that transient adenylation can occur in the cytoplasm as well, as such molecules were detected in cytoplasmic fractions. However, in yeast, unstable transcripts derived from intergenic regions (i.e., nuclear) were reported to be stabilized upon inhibition of Xrn1 and Dcp1 (i.e., cytoplasmic).…”
Section: Exosome or Hpnpase Silencing Does Not Cause A Decrease In Thementioning
confidence: 69%
See 3 more Smart Citations
“…A nuclear RNA surveillance mechanism involving polyadenylation and rapid degradation of nonfunctional, antisense, and noncoding RNAs has been described in yeast and human cells (4,9,(33)(34)(35)(36). We initially assumed that the truncated, polyadenylated rRNA molecules that we had previously detected in human cells (18) are solely related to this process, but in this study we found that transient adenylation can occur in the cytoplasm as well, as such molecules were detected in cytoplasmic fractions. However, in yeast, unstable transcripts derived from intergenic regions (i.e., nuclear) were reported to be stabilized upon inhibition of Xrn1 and Dcp1 (i.e., cytoplasmic).…”
Section: Exosome or Hpnpase Silencing Does Not Cause A Decrease In Thementioning
confidence: 69%
“…In earlier work, we detected truncated 28S and 18S rRNAs containing homo-or heteropolymeric tails (18). It was plausible that these rRNA fragments are degradation intermediates of the nuclear process mentioned earlier, but a second option could not be ignored: transient, perhaps degradation-assisting, adenylation of RNA within the cytoplasm, coexisting with the stable poly(A) tails that characterize this cellular location.…”
Section: Fragmented 28s Rrna Molecules Containing Homo-or Heteropolymmentioning
confidence: 79%
See 2 more Smart Citations
“…When PNPase or the archaeal exosome is the polymerizing enzyme, heteropolymeric tails composed mostly of adenosine but also of other nucleotides are produced [5,8,36,66]. Heteropolymeric tails were also recently identified in human cells [67].…”
Section: The Biological Function Of Pnpase and Exosomementioning
confidence: 99%